Intra-Abdominal Testicular Seminoma in a Woman with Testicular Feminization Syndrome - Darshana D. Rasalkar; Bhawan K. Paunipagar; Alex Ng; Fernand M. Lai; Shalini Jain Bagaria (Case Reports in Radiology)
We report a case of intra-abdominal testicular tumor in a 36-year-old married lady presenting with chief complaints of primary amenorrhea. The patient was later diagnosed with testicular feminization syndrome, a form of male pseudohermaphroditism. This testicular tumor was histologically proven as seminoma. Due to rarity, imaging findings in patients with testicular feminization syndrome and intraabdominal testicular tumor have been poorly documented. So far, only one case report had described the combined role of CT and MR imaging in intraabdominal testicular sex-cord stromal tumor. To our knowledge, this case is first to document USG and MR imaging in addition to MR spectroscopy features in intraabdominal testicular seminoma.